DINAMIKA KEKUASAAN PADA MASA DAULAH ABBASIYAH: ANALISIS MATERI AJAR DI SEKOLAH MENENGAH - Putriyana Rahayu; Hanifa Chaerani; Ariesta Widia Kriesta; Tiar Anwar Bachtiar (LPPM Universitas Cipta Mandiri, 2026)
Islamic Cultural History (SKI) learning at the secondary school level remains largely dominated by chronological-descriptive and moralistic approaches, limiting students' analytical development. This study aims to analyze the dynamics of Abbasid political power in contemporary academic literature, examine their representation in SKI teaching materials at the MTs and MA levels, and formulate a reconstruction grounded in historical thinking. A Systematic Literature Review (SLR) based on PRISMA 2020 guidelines was employed, drawing from Google Scholar, Scopus, Dimensions, Crossref, DOAJ, Garuda, and Moraref. Of 150 documents identified, 15 primary sources were analyzed through thematic synthesis. Findings indicate that contemporary historiography views the Abbasid Caliphate as a complex political phenomenon marked by power centralization, transformation of caliph-military relations, political fragmentation, and the development of Islamic political thought. Analysis of SKI materials reveals a significant gap between modern historiography and existing linear-moralistic representations. This study proposes a reconstruction of teaching materials emphasizing historical causality, the use of Islamic primary sources, and the connection between Abbasid political experience and contemporary issues.